Soil invertebrate diversity in coffee-pine agroforestry system at Sumedang, West Java - IDA KINASIH; TRI CAHYANTO; ANA WIDIANA; DESTI NURBAH INDAH KURNIA; UCU JULITA; RAMADHANI EKA PUTRA (Society for Indonesian Biodiversity, 2016)
Kinasih I, Cahyanto T, Widiana A, Kurnia DNI, Julita C, Putra RE. 2016. Soil invertebrate diversity in coffee-pine agroforestry system at Sumedang, West Java. Biodiversitas 17: 473-478. In order to maintain natural habitat while provide economic benefit for community near forest, some agroforestry systems were developed. This system depends on service provided by ecosystem such as nutrient cycling by soil invertebrates. One of important factors of healthy ecosystem services at particular agroecosystem is local biodiversity of the area. In this study we carried out biodiversity survey of soil invertebrates at local coffee - pine agroforestry system at Rancakalong Sub-district, Sumedang District, West Java, Indonesia. Soil invertebrates were collected from coffee plantation, coffee and pine (Pinus merkusii) plantation and pine plantation by 40 pitfall trap per location. Results showed the highest abundance was recorded at coffee plantation (2477 individuals) and the lowest was at pine plantation (1372 individuals). All collected soil invertebrates grouped into 3 classes (Arachnida, Chilopoda and Insecta), 16 orders, 47 families, and 124 morphospecies. Soil invertebrates were dominated by Formicidae, Scarabaeidae, Blattidae, Forficulidae, and Phalangiidae. The average diversity index of soil invertebrates was 2.25 (coffee plantation), 2.64 (coffee and pine plantation) and 1.85 (pine plantation). The evenness value was 0.30 (coffee plantation), 0.49 (coffee and pine plantation) and 0.39 (pine plantation). This study showed agroforestry may improve soil invertebrate abundance and diversity of monoculture pine forest through creation of additional and alternative nutrition and microhabitats.